PENERAPAN METODE TEOREMA BAYES UNTUK MENDETEKSI HAMA PADA TANAMAN PADI MAYAS KALIMANTAN TIMUR - Novianti Puspitasari; Hamdani Hamdani; Heliza Hatta; Anindita Septiarini; Sumaini Sumaini (LPPM STMIK STIKOM Indonesia, 2021)
The community very much needs the nutritional needs of food during a pandemic. One source of nutrition that can be obtained is rice or rice derived from rice plants. Mayas rice is a rice plant with advantages in terms of high taste quality and components of certain physiological functions that are beneficial to health. However, Mayas rice has quite a lot of pest attacks, thus reducing agricultural production. On the other hand, the knowledge possessed by the community regarding pests in Mayas rice is still very minimal. Hence, people find it difficult to determine the proper pest control method. Bayes theorem applied in an expert system can be a solution to diagnose the types of pests that attack Mayas rice. The research data is a knowledge base that contains 32 symptoms that appear and 10 types of pests that attack Mayas rice. The results showed that the percentage of certainty in the diagnosis of the types of pests that pounded Mayas rice was based on the symptoms given by the user. The level of testing using ten test cases displays the results of an expert system for identifying types of pests that attack Mayas rice which is suitable for use with a percentage of 90%.